Relatório de estágio em coordenação de ensaios clínicos de oncologia - Coelho, Carolina Gomes da Silva (2022)
This report was elaborated in the scope of the curricular internship in Clinical Trial Coordination at the Investigation Unit of the Francisco Gentil Oncology Portuguese Institute (IPO-Porto), as part of the Master of Clinical Investigation Coordination from Lisbon Nova Medical School in partnership with University of Aveiro. The internship took place between September 2021 and February 2022. Its main objectives were the application and deeper understanding of the knowledge acquired during the previously referred Master’s degree, as well as experiencing a real-life context of application of said knowledge in the practical aspects of clinical investigation and, more specific, the coordination of clinical trials. The first part of this document presents the institution in which the internship took place. It also contemplates a revision of the clinical investigation state of the art with particular relevance to the current situation and practises in Portugal. This revision also focuses the oncology area, in particular breast cancer. After that, in the document are described the activities performed in the context of clinical trial coordination in “Clínica da Mama” (“Breast Clinic”) in IPO Porto. Among these activities were the inclusion and randomization of participants, preparation and execute study visits, data entry and notifying in electronic systems, accompaniment in monitoring visits, participation in Site Initiation Visit and Close-out Visit, document filing, among others. Finally, it concludes with a critical reflexion of the work done and the conclusions obtained from this internship. During this period, it was possible to acquire new experiences, knowledge and essential skills for a future career in clinical investigation, focused on clinical trial coordination.